(untitled) (Medical Forum Monthly, 2022)
ABSTRACT Objective: To correlate local recurrence in oral squamous cell carcinoma with tumour size, safe margin resection and delay in post-operative adjuvant radiotherapy. Study Design: Cohort study. Place and Duration of Study: This study was conducted at the ENT Department, Jinnah Medical College Hospital, Karachi between November 2017 and December 2021. Materials and Methods: All patients presented with resectable squamous cell carcinoma of oral cavity were included in the study. These were followed-up with minimum period of two years for disease recurrence at the primary site. Results: Total 116 patients were included in the study, out of which 29(25%) were females and 87(75%) were males with mean age of 48.8 ± 8.2 years. Most common site was buccal mucosa 64(55.1%) and moderately differentiated carcinoma on histopathology 96(82.8%). Local recurrence rate was 0% in T1, 8.6% in T2, 19.1% in T3 and 40.0% in T4 lesions (p-value = 0.001), 1.6% where safe margin is > 10 mm, 34.7% where margins are between 1 to 5 mm and 100% where < 1 mm (p-value = 0.002). Similarly recurrence rate was 5.5% when adjuvant radiation started within 1 month, 4.8% when started between 1 to 3 months, 30.4% when between 3 to 6 months and 78.5% when started > 6months after primary surgery (p-value = 0.001). Conclusion: There are higher local recurrence rate in patient presenting with advanced T-stage disease, less distance of tumour from the resected margins and delay in initiation of post-operative adjuvant radiation therapy.